Tumor-infiltrating lymphocytes provides recent survival information for early-stage HER2-low-positive breast cancer: a large cohort retrospective study - Sun, Teng; Wang, Tong; Li, Xiangjun; Wang, Haibo; Mao, Yan (Frontiers in Oncology, 2023)
Purpose It has been reported that breast cancer (BC) with low expression of human epidermal growth factor receptor 2 (HER2) might be a distinct subtype of BC. However, the prognostic effect of low HER2 expression on BC patients remains controversial. We aim to conduct this single-institution retrospective analysis to assess HER2-low-positive BC outcomes in Chinese women and the prognostic role of TILs in HER2-low-positive early-stage BC. Method We retrospectively enrolled 1,763 BC patients treated in a single institution from 2017 to 2018. TILs are regarded as continuous variables and are divided into low TILs (≤10%) and high TILs (>10%) for statistical analysis. Univariate and multivariable Cox proportional hazards regression models were used to test the associations between TILs and disease-free survival (DFS) with adjustment for clinicopathologic characteristics. Result High TIL levels (>10%) were associated with tumor size (>2 cm, p = 0.042), age at diagnosis (p = 0.005), Ki-67 index (>25%; p <0.001), HR (hormone receptor) status (positive, p <0.001), advanced pathological stage (p = 0.043), subtype (p <0.001), and HER2 status (p <0.001). The Kaplan−Meier analysis indicated that no significant difference in DFS (p = 0.83) could be found between HER2-positive, HER2-low-positive, and HER2-0 BC. The DFS of HER2-low-positive BC and HER2-nonamplified BC with high levels of TILs was statistically better than that of patients with low levels of TILs (p = 0.015; p = 0.047). In HER2-low-positive BC patients with high TIL levels (>10%), DFS was significantly improved in both the univariate (HR = 0.44, 95% CI 0.22–0.87, P = 0.018) and multivariate (HR = 0.47, 95% CI 0.23–0.95, P = 0.035) Cox models. For further subgroup analysis, HR (+)/HER2-low-positive BC with high TIL (>10%) levels was associated with improved DFS in both the univariate (HR = 0.41, 95% CI 0.19–0.90, P = 0.025) and multivariate (HR = 0.42, 95% CI 0.19–0.93, P = 0.032) Cox models. The HR (−)/HER2-0 BC with high TIL (>10%) level was not statistically significant in the univariate Cox model, but it was statistically significant in the multivariate (HR = 0.16, 95% CI 0.28–0.96, P = 0.045) Cox model. Conclusion Among early-stage BC, no significant survival difference could be found between the HER2-positive, HER2-low-positive, and HER2-0 cohorts. High levels of TILs were significantly associated with improved DFS in HER2-low-positive patients, especially in the HR (+)/HER2-low-positive subtype.